Microsoft Visual Web Developer 2008 Express Edition - Griffin, Eric, 1968- (Redmond, Wash.: Microsoft Press, 2007)
Teach yourself Visual Web Developer 2008--one step at a time. Ideal for beginning developers who want to design modern, dynamic Web sites, this practical tutorial delivers hands-on guidance for creating data-driven pages that integrate Web services and ASP.NET controls. Discover how to: Design a sample Web portal and configure site security Use Master Pages to create a consistent look and feel Attach a style sheet to an ASP.NET page and apply styles Use server controls for greater flexibility and maintainability Incorporate HTML and JavaScript editing capabilities Create a database and design a user interface to manage it Construct a Web service and use it in an ASP.NET page Embed Microsoft Popfly(TM) mashups--and integrate APIs and data--without coding CD features: Practice exercises and code samples Fully searchable eBook A Note Regarding the CD or DVD The print version of this book ships with a CD or DVD. For those customers purchasing one of the digital formats in which this book is available, we are pleased to offer the CD/DVD content as a free download via O'Reilly Media's Digital Distribution services. To download this content, please visit O'Reilly's web site, search for the title of this book to find its catalog page, and click on the link below the cover image (Examples, Companion Content, or Practice Files). Note that while we provide as much of the media content as we are able via free download, we are sometimes limited by licensing restrictions. Please direct any questions or concerns to booktech@oreilly.com.
each yourself Visual Web Developer 2008—one step at a time. Ideal for beginning developers who want to design modern, dynamic Web sites, this practical tutorial delivers hands-on guidance for creating data-driven pages that integrate Web services and ASP.NET controls. Discover how to: Design a sample Web portal and configure site security Use Master Pages to create a consistent look and feel Attach a style sheet to an ASP.NET page and apply styles Use server controls for greater flexibility and maintainability Incorporate HTML and JavaScript editing capabilities Create a database and design a user interface to manage it Construct a Web service and use it in an ASP.NET page Embed Microsoft Popfly$1!" (Bmashups—and integrate APIs and data—without coding CD features: Practice exercises and code samples Fully searchable eBook A Note Regarding the CD or DVD The print version of this book ships with a CD or DVD. For those customers purchasing one of the digital formats in which this book is available, we are pleased to offer the CD/DVD content as a free download via O'Reilly Media's Digital Distribution services. To download this content, please visit O'Reilly's web site, search for the title of this book to find its catalog page, and click on the link below the cover image (Examples, Companion Content, or Practice Files). Note that while we provide as much of the media content as we are able via free download, we are sometimes limited by licensing restrictions. Please direct any questions or concerns to booktech@oreilly.com.s
Introduction -- Who This Book Is For -- Finding Your Best Starting Point in This Book -- Conventions and Features in This Book -- Hardware and Software Requirements -- Code Samples Support for This Book -- Chapter 1: Introducing Visual Web Developer 2008 -- Chapter 2: Working in Visual Web Developer 2008 -- Chapter 3: Creating Your First ASP.NET Page -- Chapter 4: Creating Your First Web Site -- Chapter 5: Using Master Pages -- Chapter 6: Using Server Controls -- Chapter 7: Working with HTML and JavaScript -- Chapter 8: Working with Database -- Chapter 9: Building Data-Driven User Interfaces -- Chapter 10: Using Cascading Style -- Chapter 11: Understanding and Using Mashups -- Chapter 12: Working with Web Services -- Chapter 13: Deploying Your Web Site
Includes index.
1
Keywords: Microsoft Windows (Computer file); Operating systems (Computers); VBScript (Computer program language)